RETRACTED: The influence of cyclic temperature and humidity effects on the compressive strength of heavy concrete - Garanzha Igor; Tanasoglo Anton; Pisareva Milena; Gorokhov Yevgeniy; Smirnova Natalia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001